Paramedics on and off the streets : emergency medical services in the age of technological governance - Corman, Michael K. (Michael Kenneth), 1982- (University of Toronto Press, 2017)
"In Paramedics On and Off the Streets, Michael K. Corman embarks on an institutional ethnography of the complex, mundane, intricate, and exhilarating work of paramedics in Calgary, Alberta. Corman's comprehensive research includes more than 200 hours of participant observation ride-alongs with paramedics over a period of eleven months, more than one hundred first hand interviews with paramedics, and thirty-six interviews with other emergency medical personnel including administrators, call-takers and dispatchers, nurses, and doctors. At the heart of this ethnography are questions about the role of paramedics in urban environments, the role of information and communication technologies in contemporary health care governance, and the organization and accountability of pre-hospital medical services. Paramedics On and Off the Streets is the first institutional ethnography to explore the role and increasing importance of paramedics in our healthcare system. It takes readers on a journey into the everyday lives of EMS personnel and provides an in-depth sociological analysis of the work of pre-hospital health care professionals in the twenty-first century."--